Numerical Investigations on Temperature Distribution and Evolution of Cavitation Bubble Collapsed Near Solid Wall - Shan, Minglei; Yang, Yu; Kan, Xuefen; Shu, Fangyong; Han, Qingbang (Frontiers in Energy Research, 2022)
The internal temperature distribution and evolution in cavitation bubble can be investigated numerically by a thermal lattice Boltzmann method. The simulation results are consistent with the calculational results of the Rayleigh-Plesset equation and the temperature equation when the cavitation bubble collapses in an infinite liquid medium and satisfy Laplace’s law. In this work, a cavitation bubble collapsing near a solid wall is explored to investigate the characteristics and effects of the bubble temperature. The progress of the bubble temperature can be clearly captured from a two-dimensional temperature field. The results show that the bubble temperature can reach extremely high values during both its first and its second collapse. The change of the bubble temperature is highly related to the jet velocity and the liquid pressure. Furthermore, the effects on the bubble temperature of the offset parameters, the initial driving pressure and the initial bubble radius are also studied. The present findings are meaningful for the research of thermodynamics of cavitation.